Let us solve the equation "\\frac{d^2y}{dx^2}+\\frac{1}{x}\\frac{dy}{dx}=12\\frac{\\ln x}{x^2}".
Let us multiply both part by "x": "x\\frac{d^2y}{dx^2}+\\frac{dy}{dx}=12\\frac{\\ln x}{x}". Then
"\\frac{d}{dx}(x\\frac{dy}{dx})=12\\frac{\\ln x}{x}" and therefore,
"x\\frac{dy}{dx}=12\\int \\frac{\\ln x}{x}dx=12\\int \\ln x\\ d(\\ln x)=6\\ln^2x+C_1"
Let us divide both part by "x":
"\\frac{dy}{dx}=6\\frac{\\ln^2x}{x}+\\frac{C_1}{x}"
Consequently,
"y=6\\int(\\frac{\\ln^2x}{x}+\\frac{C_1}{x})dx=6\\int\\ln^2x\\ d(\\ln x)+6C_1\\int\\frac{dx}{x}=2\\ln^3 x+6C_1\\ln x+C_2"
Answer: "y=2\\ln^3 x+6C_1\\ln x+C_2"
Comments
Leave a comment